2011
DOI: 10.1007/s10592-011-0202-4
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale genetic structure of an endangered population of the Mormon metalmark butterfly (Apodemia mormo) revealed using AFLPs

Abstract: We investigated the genetic structure and diversity of an endangered Canadian population of the Mormon metalmark butterfly (Apodemia mormo) using, for the first time, amplified fragment length polymorphism (AFLP) markers generated from non-lethal samples of butterfly wing tissue. Based on 326 loci, our analyses show a high degree of spatial genetic structure within the population, indicating limited gene flow, despite a small geographic range (\20 km). We found that geographic distance, particularly measured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 53 publications
(61 reference statements)
0
23
0
Order By: Relevance
“…We suspect that the skewed distribution of locus-specific error rates observed here is not unusual, compromising average genotyping error as a sole criterion for choosing a final data set. Others have noted the same thing, for example, by removing 'singleton' loci from the optimum data set as judged with AFLPSCORE (Crawford et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We suspect that the skewed distribution of locus-specific error rates observed here is not unusual, compromising average genotyping error as a sole criterion for choosing a final data set. Others have noted the same thing, for example, by removing 'singleton' loci from the optimum data set as judged with AFLPSCORE (Crawford et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In our experience using these methods, it is rarely clear which thresholds are more desirable, those giving lower average error and smaller data sets or those yielding higher error and larger data sets, but they make it possible to explore trade-offs using objective and repeatable criteria. Two studies that have used these tools to compare population genetic informativeness of low and high stringency data sets found that the latter, with fewer scored loci, seemed to provide slightly more explanatory power with respect to population structure (Herrmann et al, 2010;Crawford et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jefferson (Anthony 1970;McFarland 2003). Some butterflies show a low ability or propensity to disperse among such fragmented habitat patches (e.g., Brussard et al 1974;Britten et al 1995;Vandewoestijne and Baguette 2004;Keyghobadi et al 2006;Sigaard et al 2008;Leidner and Haddad 2010;Crawford et al 2011;Polic et al 2014), and historically, few WMA adults have been observed in areas of the alpine zone between meadows (McFarland 2003). This suggests that dispersal, and hence, gene flow, may be limited among meadows for the WMA (Anthony 1970;McFarland 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As such, genetic data would be particularly useful for studying and characterizing the WMA population and enabling conservation plans to be developed. Not only are genetics now recognized to play a major role in the fates of threatened populations (Spielman et al 2004;Frankham 2010), but molecular data also can be used to infer behavioural and demographic characteristics that may not otherwise be easily discernible or attainable through traditional monitoring (Charman et al 2010;Darvill et al 2010;Crawford et al 2011). Thus far, genetic analysis has played an indispensable role in the study of numerous endangered butterfly populations (Harper et al 2003;Vandewoestijne and Baguette 2004;Gompert et al 2006;Sigaard et al 2008;Habel et al 2010b;Crawford et al 2011;Kodandaramaiah et al 2012).…”
Section: Introductionmentioning
confidence: 99%